SIMBOL PERAYAAN TAHUN BARU KEBUDAYAAN RUSIA DALAM FILM ANIMASI SERIAL TELEVISI СМЕШАРИКИ/SMESHARIKI (BOLA KECIL LUCU) - Maharani, Jasmine Aisyah, J; Limbong, Banggas, M.Hum. (Multikultura, 2025)
This final project is a study on the meaning of the New Year's symbols found in the animated series Смешарики/Smeshariki (cute little balls) New Year's edition. This type of research is qualitative with a descriptive analysis method. This research refers to the study of the meaning of the symbols of New Year's celebration in Russia found in the animated series Смешарики/Smeshariki (cute little balls) New Year's edition, because in the animated series Смешарики/Smeshariki (cute little balls) New Year's edition there are elements of symbols that can represent the traditions or customs of Russian society in celebrating the New Year. The symbols of New Year's celebrations found in the animated series Смешарики/Smeshariki (cute little balls) New Year's edition have an indirect educational purpose, namely to provide knowledge about the traditions or customs of Russian society in celebrating the New Year in Russia which can be said to be "unique" because it has different customs when compared to the traditions of New Year's celebrations in general. through children's animation. By examining the meaning of the symbols of New Year's celebrations found in the animated series Смешарики/Smeshariki (cute little balls) New Year's edition, it is hoped that it can provide information that is more easily accepted by the general public outside Russia about the culture of New Year's celebrations in Russia.